The dose-response relationship between BMI and hypertension based on restricted cubic spline functions in children and adolescents: A cross-sectional study - Yani Wang; Congcong Min; Xiaoyan Song; Heyue Zhang; Chen Yuan; Lizhen Chen; Haiying Zhang (Frontiers Media S.A., 2022)
BackgroundA high body mass index (BMI) is a major risk factor for hypertension. The purpose of this study was to investigate the association between the BMI and hypertension in children and adolescents.MethodsWe analyzed physical examination data from 29,810 students aged 6-14 years old. A restricted cubic spline (RCS) function was used to investigate the dose-response relationship between the BMI and hypertension.ResultsThe prevalence of hypertension was 9.91%, followed by 11.71% in males and 7.9% in females, respectively. Compared to the normal weight group, the odds risk (OR) for hypertension in the overweight group was 1.729, and the OR for hypertension in the obesity group was 3.089. After adjusting for potential confounders, the adjusted ORs were 1.620 [95% confidence interval (CI): 1.457-1.800] in the overweight group and 3.092 (95% CI: 2.824-3.385) in the obesity group. According to the multivariate RCS regression analysis, there was a significant non-linear dose-response association between the BMI and the risk of hypertension (all P-values for non-linear < 0.001).ConclusionThe dose-response relationship analysis showed that the association strength of hypertension increased non-linearly along with the continuous change of BMI in children and adolescents.